Model of Deposit and Loan of A Bank Using Spiral Optimization Algorithm - Moch Fandi Ansori; Kuntjoro Adji Sidarto; Novriana Sumarti (Journal of the Indonesian Mathematical Society, 2019)
Nowadays, the study of financial stability of banking is important, which is to observe the behavior of the bank in the future. In this paper, a simple model of deposit and loan of a bank is solved analytically and numerically, and then it is implemented into data of four groups of commercial banks in Indonesia based on their capitals. From the data for each group of banks, the parameters will be estimated using the Spiral Optimization Algorithm. The results show that the algorithm gives satisfactory solutions in terms of closeness between the analytical and numerical solutions. In the long run, the deposit and loan volumes will be stable at their equilibrium points which showing the good condition of the future of the banks based on current state.